Co-transfer of last-line antibiotic resistance and virulence operons by an IncFIBk-FII-X3-ColKP3 hybrid plasmid in Klebsiella pneumoniae. (21st April 2022) - Liu, Congcong; Dong, Ning; Zeng, Yu; Lu, Jiayue; Chen, Jiawei; Wang, Yao; Cai, Chang; Chen, Kaichao; Chen, Gongxiang; Shen, Zhangqi; Chen, Sheng; Zhang, Rong
Abstract: Objectives: To characterize a clinical Klebsiella pneumoniae isolate from China co-harbouring tet (X4), bla OXA-181 and the aerobactin operon on an IncFIBk -FII-X3-ColKP3 hybrid plasmid. Methods: A tigecycline-resistant strain was recovered from the intestinal sample of a patient. It was subjected to antimicrobial susceptibility testing, conjugation assay, virulence testing, WGS, bioinformatics analysis, plasmid stability testing and fitness cost testing. Results: The strain K. pneumoniae T877 was resistant to tigecycline, intermediate to piperacillin/tazobactam and ertapenem, and positive for tet (X), bla OXA-181 and the virulence-associated operon iutAiucABCD, which were located on the same plasmid, named pKPT877-hybrid. It was 99.96% identical to the IncFIBk -FII plasmid pSCH6109-Vir (accession number CP050860) from K. pneumoniae strain SCH6109 at 96% coverage with the absence of a 50 kb region on pKPT877-hybrid; this region was highly homologous to the 51 kb IncX3-ColKP3-type, bla OXA-181 -carrying plasmid pOXA181-191773 (accession number CP080367). Plasmid pKPT877-hybrid was conjugatively transferable to the ST11 K. pneumoniae strains FJ8 and KP04. pKPT877-hybrid did not have a significant impact on the fitness cost and could be maintained stably in T877. Conclusions: We report for the first time (to the best of our knowledge) the co-transfer of last-line antibiotic resistance determinants [ tet (X4) and bla OXA-181 ] and the aerobactin operon ( iutAiucABCD ) by a mobile IncFIBk -FII-X3-ColKP3 hybrid plasmid, which can be stably maintained in K. pneumoniae strains, even in the absence of antibiotic selective pressure. Once the plasmid transfers to a K. pneumoniae with porin deficiency, the strain might have high levels of resistance to carbapenems and tigecycline, which are the last line of defence against infections. Heightened and continuous efforts are needed to control its dissemination.